2021
DOI: 10.33073/pjm-2021-039
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Infections in COVID-19 Intensive Care Patients

Abstract: Opportunistic fungal infections increase morbidity and mortality in COVID-19 patients monitored in intensive care units (ICU). As patients’ hospitalization days in the ICU and intubation period increase, opportunistic infections also increase, which prolongs hospital stay days and elevates costs. The study aimed to describe the profile of fungal infections and identify the risk factors associated with mortality in COVID-19 intensive care patients. The records of 627 patients hospitalized in ICU with the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…All of the papers were observational in design (n=38), of which 10 were prospective [15][16][17]19,24,36,40,41,44,48] and 26 retrospective studies [18,[20][21][22][23][25][26][27][28][29][30][31][32][33][34][35][37][38][39]42,43]. Among them, 8 studies were classified as case-series [18,21,22,27,37,40,45,47]. The 2 remaining studies were both prospective and retrospective in design [50,52].…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…All of the papers were observational in design (n=38), of which 10 were prospective [15][16][17]19,24,36,40,41,44,48] and 26 retrospective studies [18,[20][21][22][23][25][26][27][28][29][30][31][32][33][34][35][37][38][39]42,43]. Among them, 8 studies were classified as case-series [18,21,22,27,37,40,45,47]. The 2 remaining studies were both prospective and retrospective in design [50,52].…”
Section: Study Selectionmentioning
confidence: 99%
“…By implementing NOS, we assessed 30 analytical studies (the remaining 8 studies were descriptive in design). Overall, we identified 12 studies of "good" quality [15,22,27,28,36,41,45,46,48,[50][51][52] and 18 studies of "poor" quality [16][17][18][19][20][21][23][24][25][26][29][30][31][32][33][34][35][37][38][39][40][42][43][44]47,49]. The majority of studies were deemed to be lacking in terms of "Comparability" criterion, as the aforementioned 26 studies did not control for any confounding factors (Supplementary Table 2).…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…As antibiotic use may disrupt the balance between oral bacterial and yeast populations, it can create an environment that permits candida overgrowth and infection [ 91 ]. Clinicians in Turkey observed that COVID-19 patients who were receiving broad-spectrum antibiotics were at an increased risk for developing candidemia [ 92 ]. In COVID-19 treatment guidelines, the World Health Organization recommends against the use of broad-spectrum antibiotics unless there is a clinical suspicion of bacterial infection [ 93 ].…”
Section: Fungal Coinfectionsmentioning
confidence: 99%